Characterization of indoor air mycobiota of two locals in a food industry, Cuba - Anaya, Matilde (2019)
The aim of this work was to characterize the air mycobiota of two production plants, one of artisanal chocolate and another of products for special regimes in a food factory in Cuba at different times of the year. The air was sampled during 1 year every 25 days distributed in rainy season and non-rainy. The method proposed by Omeliansky was applied and four bacteriostats were used: chloramphenicol, lactic acid, sodium chloride, and iodized common salt with malt agar extract in Petri dishes exposed for 1 h. The temperature and relative humidity were monitored to determine their influence on the fungal concentration, which was higher in the rainy season. Among the main fungi isolated from the air mycobiota of these production plants, Neurospora crassa was the predominant species along with the genera Aspergillus and Trichoderma. In addition, other less frequent genera as Cladosporium and Fusarium were detected. However, Penicillium and Mucor were predominant and non-frequent in the artisanal chocolate area. The adequate constructive design of the production plants and the correct location of dehumidifiers were identified as important elements to decrease the fungal contamination. Likewise, this study suggests the use of iodized salt as an economic alternative in air microbiological sampling of indoor environments.